The Influence of Green Supply Chain Management on Financial, Environmental and Operational Performance - Fawzia, Diana (International Journal of Supply Chain Management, 2020)
The financial along with financial, environmental and operational performance is the essential part of organizational success and economic growth while green supply chain management is considered as the essential element for the financial, environmental and operational performance. Thus, the present study has examined the green supply chain management impact on the financial, environmental and operational performance of the manufacturing organization in Indonesia. The aim of the current article also includes the examination of the mediating role of environmental and operational performance among the nexus of green supply chain management and financial performance. The data of the existing study has been obtained from the employees that are related to the supply chain practices of manufacturing companies through questionnaires and smart-PLS was used for analysis purpose.  The results revealed that green supply chain along with operational and environmental performance has a positive association with financial performance. The findings also exposed that the green supply chain also has positive nexus with operational and environmental performance while operational and environmental performance positively mediates among the nexus of green supply chain and financial performance. These findings provided the guidelines to the policy-makers that they should develop as well as implement the favorable policies that could increase the supply chain performance and impact on the overall performance of the organization.